Skeleton Key - Horowitz, Anthony, 1955- (London : Walker Books, 2012)
Reluctant teenage-spy Alex Rider, on a routine mission at the Wimbledon tennis championships, gets caught up in Chinese gangs, illegal nuclear weapons, and the suspect plans of his Russian host, General Sarov.
Booklist
School Library Journal
Wilson's Junior High School
5.1
5-8.
5-8
Keywords: Orphans -- Fiction; Spies -- Fiction; Tennis -- Fiction; Terrorism -- Fiction; Orphans -- Fiction; Spy stories; Tennis -- Fiction; Terrorism -- Fiction; England -- Fiction; England -- Fiction